Enhancing the intermediate vision of monofocal intraocular lenses using a higher order aspheric optic - Alarcon, Aixa; Cánovas, Carmen; Koopman, Bram; Weeber, Henk; Auffarth, Gerd U.; Piers, Patricia A. (Journal of refractive surgery, 2020)
Purpose: To describe and evaluate a new monofocal intraocular lens (IOL) designed to improve intermediate vision using a unique refractive technology. Methods: The new monofocal lens is based on a higher order aspheric optic and is designed to improve intermediate vision. Simulated visual acuity from far to −2.00 diopters (D) was calculated using optical bench data. The effect of corneal higher order aberrations (HOAs) on simulated visual acuity, pupil size, and decentration was assessed using realistic computer eye models. The susceptibility to photic phenomena was evaluated by measuring preclinically the intensity of the light distribution in the retinal plane. The new lens design was compared to a standard aspheric monofocal IOL that shares the same platform, material, and primary spherical aberration as the new design. Results: Simulated defocus curves showed increased simulated visual acuity in the intermediate range compared to a standard aspheric monofocal IOL with comparable distance vision, independently of the pupil size and corneal HOAs. At −1.50 D, the new IOL design provided a gain of approximately 0.1 logMAR, whereas at distance, the difference was less than 0.05 logMAR. The tolerance to decentration was also similar in both designs. Finally, experimental results indicate that the susceptibility to photic phenomena with the new lens design was similar to that of a standard aspheric monofocal IOL. Conclusions: Preclinical data showed that the new lens design improves intermediate vision while maintaining comparable distance image quality and keeping the same photic phenomena profile as a standard aspheric monofocal IOL.